Immunotherapy of melanoma. Issue 3 (March 2017) - Kee, D.; McArthur, G.
Abstract: Immunotherapy for advanced melanoma has progressed dramatically in the last five years with the approval of immune checkpoint inhibitors targeting cytotoxic T lymphocyte-associated protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1). Inhibition of these targets can break cancer-immune tolerance and result in durable objective responses with significantly improved tolerability over cytokine-based immunotherapy. Ipilimumab is an inhibitor of CTLA-4 and the first-in-class immune checkpoint inhibitor to demonstrate an improvement in overall survival in melanoma. Pembrolizumab and nivolumab target PD-1 and have improved single agent activity and tolerability in comparison to ipilimumab. The combination of nivolumab and ipilimumab results in even better response rates, reductions in tumor volume and progression free survival but at the expense of considerable autoimmune effects. Autoimmune side-effects and non-standard response kinetics represent a new challenge associated with cancer therapies that practitioners will have to become more familiar with as checkpoint inhibitors increasingly become part of mainstream oncological practice. Ongoing areas of investigation include drug development against novel immune targets; alternative treatment modalities, such as genetically modified oncolytic viruses; optimization of immunotherapy combination strategies; and the identification of reliable biomarkers to better guide treatment selection.